Informal HCI: Fixing Playability Issues As A Strategy To Improve The Skills Of Novice Programmers - Barcelos, T.S.; Costa, G.C.; Munoz, R.; Silveira, I.F. (Revista IEEE América Latina, 2014)
Human-Computer Interaction topics have been previously used to motivate and attract students to the field of Computer Science. However, as students are growing up in contact with several interactive computational devices, one could suspect that they already possess an empirical, informal knowledge about the quality of some specific types of human-computer interfaces. This informal knowledge may influence how these students deal with the construction of interactive artifacts while learning programming fundamentals. In order to test this hypothesis, we developed a Game Design Workshop to be offered to high school students. Based on the results of its first offering, we identified that issues related to displaying the game status and score, response time of controls and graphical and sound features were quite relevant to students. Students added additional features to solve those issues in a spontaneous way. An analysis of the developed games indicates that, in order to implement the additional features, students had to learn and apply programming concepts that were new to them, such as loop boundaries and message broadcasting.